2020
DOI: 10.1590/1983-21252020v33n320rc
|View full text |Cite
|
Sign up to set email alerts
|

Production and Quality of Mini Watermelon Under Drip Irrigation With Brackish Water

Abstract: Watermelon plays an important role in Brazilian agribusiness. The objective of present study was to evaluate the effect of different irrigation managements and water salinity levels, on the main productive and postharvest characteristics of mini-watermelon (Citrullus lanatus) cv. ‘Sugar Baby’. The experiment was conducted in a greenhouse in a completely randomized design, arranged in a 2 x 4 factorial scheme, with four replicates. The treatments consisted of two types of irrigation management (conventional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In addition, salt stress affects the fruit yield of crops because it causes changes in plant physiology in response to factors such as osmotic stress, ionic toxicity and nutritional imbalance (Negrão et al, 2017). Do Ó et al (2020), in a study evaluating the effect of pulse and drip irrigation management and water salinity levels (ECsol ranging from 2.5 to 6.5 dS m -1 ), on the productive and postharvest characteristics of Sugar Baby mini-watermelons, obtained fresh mass of 1,193 g of fruits in the plants cultivated under ECsol of 6.5, that is, a value higher than that used in the present study. It is worth mentioning that Do Ó et al (2020) used as substrate mixture of coconut fiber and bovine manure in the proportion of 3:1 (volume basis), which might have mitigated the action of the matric potential on the availability of water for the plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, salt stress affects the fruit yield of crops because it causes changes in plant physiology in response to factors such as osmotic stress, ionic toxicity and nutritional imbalance (Negrão et al, 2017). Do Ó et al (2020), in a study evaluating the effect of pulse and drip irrigation management and water salinity levels (ECsol ranging from 2.5 to 6.5 dS m -1 ), on the productive and postharvest characteristics of Sugar Baby mini-watermelons, obtained fresh mass of 1,193 g of fruits in the plants cultivated under ECsol of 6.5, that is, a value higher than that used in the present study. It is worth mentioning that Do Ó et al (2020) used as substrate mixture of coconut fiber and bovine manure in the proportion of 3:1 (volume basis), which might have mitigated the action of the matric potential on the availability of water for the plants.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies carried out with watermelons under conditions of salt stress highlighted the sensitive nature of the crop to the salinity of irrigation water (Sousa et al, 2016;Silva et al, 2020;Lima et al, 2020a). However, the effect of salt stress on plants may vary according to the stages of plant development, as well as fertilization management practices, irrigation and climatic conditions (Lemes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to evaluate the potential of using saline water in the cultivation of mini watermelon and have found the harmful effects of water salinity on growth, gas exchange, photosynthetic pigments, quantum yield, biomass, production and postharvest quality 2020b;Gomes do Ó et al, 2020;Silva et al, , 2021, highlighting that the crop is sensitive to salt stress. Silva et al (2021) evaluating the effects of water salinity as a function of the phenological stages of mini watermelon found that the intensity of stress depends on irrigation management, species and/ or cultivar, irrigation and fertilization management, and climatic conditions in the region.…”
Section: Methodsmentioning
confidence: 99%
“…Excess dissolved salts in the soil solution inhibit plant growth by limiting water uptake through osmotic effects, altering metabolism, nutrient uptake, and ionic balance, ultimately affecting productivity and postharvest quality (Zhang et al, 2019;Gomes do Ó et al, 2020). In this context, the use of brackish water in agriculture has been adopted to mitigate salt stress on plants, optimize water resource use, an d m ax im i ze ag ri c u ltu ra l productivity.…”
Section: Received On January 16 2023; Accepted On November 23 2023mentioning
confidence: 99%